ANALISIS RENCANA ANGGARAN BIAYA (RAB) MENGGUNAKAN METODE AHSP DI KABUPATEN WONOGIRI TAHUN 2024 - Annisa Azhar Firdausi; Kurniawan, Arif; Himawan, Faiz Rifqi; Mulyarahman, Febryka Jati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
The Budget Plan (RAB) is an important stage in a construction project, for this reason a detailed calculation is needed so that it can be used as a guide in implementing construction. A mosque located in Gumarto, Girimarto, Girimarto District, Wonogiri Regency will be built but does not yet have a detailed RAB. The purpose of this study is to analyze the building budge tplan. The method used to calculate is the Work Unit Price Analysis (AHSP) method for Wonogiri Regency in 2024 for Cipta Karya, with the work volume is calculated with SketchUp 3D and the RAB calculation is summarized in Ms. Excel. AHSP was obtained from the Dinas Pekerjaan Umum (DPU) of Wonogiri Regency. The result of this analysis in total RAB for mosque construction work in Gumarto, Girimarto, Girimarto District, Wonogiri Regency, Central Java is IDR. 325,374,722.25 which, if added with 11% Value Added Tax (VAT), becomes Rp. 361,165,941.70 and rounded up to Rp. 361,500,000.00.